Acceptable Risk in Military Bridge Evaluation (Advances in Military Technology, 2016)
In military bridge evaluation, acceptable life-safety risk in crossings should be aligned with the acceptable life-safety risk of the associated military operation.  A continuum of acceptable life-safety risk exists for military operations, thus a continuum of acceptable life-safety risk for military vehicles crossing bridges exists.  The paper relates military mission life-safety acceptable risk levels to acceptable bridge crossing life-safety risk in an approximate quantitative manner. A continuum of acceptable life-safety risk for military bridge crossings provides flexibility in mission planning and execution, while providing engineers a basis to conduct military bridge evaluation that is consistent with the mission intent.
Keywords: acceptable risk; bridge evaluation; life-safety; military risk; operations